Parents’ perceptions on previous and current science education system in Japan - Kseniya Fomichova; Taku Misonou (University of Muhammadiyah Malang, 2018)
Parents’ views, beliefs, and experiences greatly affect children’s attitudes toward education. The research aimed to identify the parents’ perception in the past, present, and their desired priorities in science education as well as investigated the adolescents’ perceptions based on gender and academic performance on science. As a survey study, this research relied on a questionnaire as the primary method of data collection which the data gained then was analysed by using statistical descriptive (percentage). The results showed that the priorities in education have shifted toward physics and chemistry in recent decades. Moreover, biology and earth science were found to be perceived as ‘easy’ and ‘secondary’ areas in comparison to the ‘superior’ ones (physics and chemistry). This has been strengthened by the critical situation for earth science, as the education system of Japan often does not al low the students to select it. Thus, the parents wished for a more balanced system. There was a difference in adolescents’ perceptions of science areas based on gender and academic performance. Physics and chemistry were associated with boys and top performers, while biology and earth science were supposed to ‘fit’ girls and low performers.